Assessment of cortical damage in early multiple sclerosis with quantitative T2 relaxometry. (28th January 2016) - Gracien, René‐Maxime; Reitz, Sarah C.; Hof, Stephanie‐Michelle; Fleischer, Vinzenz; Zimmermann, Hilga; Droby, Amgad; Steinmetz, Helmuth; Zipp, Frauke; Deichmann, Ralf; Klein, Johannes C.
Abstract : T 2 relaxation time is a quantitative MRI in vivo surrogate of cerebral tissue damage in multiple sclerosis (MS) patients. Cortical T 2 prolongation is a known feature in later disease stages, but has not been demonstrated in the cortical normal appearing gray matter (NAGM) in early MS. This study centers on the quantitative evaluation of the tissue parameter T 2 in cortical NAGM in a collective of early MS and clinically isolated syndrome (CIS) patients, hypothesizing that T 2 prolongation is already present at early disease stages and variable over space, in line with global and focal inflammatory processes in MS. Additionally, magnetization transfer ratio (MTR) mapping was performed for further characterization of the expected cortical T 2 alteration. Quantitative T 2 and MTR maps were acquired from 12 patients with CIS and early MS, and 12 matched healthy controls. The lesion‐free part of the cortical volume was identified, and the mean T 2 and MTR values and their standard deviations within the cortical volume were determined. For evaluation of spatial specificity, cortical lobar subregions were tested separately for differences of mean T 2 and T 2 standard deviation. We detected significantly prolonged T 2 in cortical NAGM in patients. T 2 prolongation was found across the whole cerebral cortex and in all individual lobar subregions. Significantly higher standard deviations across the respective region of interest were found for the whole cerebral cortex and all subregions, suggesting the occurrence of spatially inhomogeneous cortical damage in all regions studied. A trend was observed for MTR reduction and increased MTR variability across the whole cortex in the MS group, suggesting demyelination. In conclusion, our results suggest that cortical damage in early MS is evidenced by spatially inhomogeneous T 2 prolongation which goes beyond demyelination. Iron deposition, which is known to decrease T 2, seems less prominent. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study evaluates cortical T 2 relaxation time at early MS stages. T 2 relaxometry is shown to be a suitable quantitative MRI surrogate for the detection and quantification of cortical damage in early MS. The analysis of the spatial variability of the parameter maps provides evidence of spatial heterogeneity of cortical damage in this collective.